Prescription of Aminoglycosides in 23 French Neonatal Intensive Care Units - Séverine Martin-Mons; Béatrice Gouyon; Séverine Lorrain; Soumeth Abasse; Cénéric Alexandre; Guillaume Binson; Roselyne Brat; Laurence Caeymaex; Yvan Couringa; Cécile Desbruyeres; Marine Dorsi-Di Meglio; Guillaume Escourrou; et al. (Antibiotics, 2021)
Background: Aminoglycosides are the most prescribed antibiotics in neonatal intensive care units (NICU). Reducing exposure to antibiotics in the NICU is highly desirable, particularly through benchmarking methods. Methods: Description of aminoglycosides prescriptions in 23 French NICU using the same computerized system over a 4-year period (2017–2020). A benchmarking program of antibiotics prescription was associated. Results: The population included 53,818 patients. Exposition rates to gentamicin and amikacin were 31.7% (n = 17,049) and 9.1% (n = 4894), respectively. Among neonates exposed to gentamicin, 90.4% of gentamicin and 77.6% of amikacin treatments were started within the 1st week of life. Among neonates exposed to amikacin, 77.6% started amikacin within the 1st week. The average daily dose of gentamicin at first prescription increased over the study period from 3.9 in 2017 to 4.4 mg/kg/d in 2020 (p < 0.0001). Conversely, the corresponding amikacin daily doses decreased from 13.0 in 2017 to 12.3 mg/kg/d in 2020 (p = 0.001). The time interval between the first 2 doses of gentamicin was mainly distributed in 3 values during the first week of life: 49.4% at 24 h, 26.4% at 36 h, and 22.9% at 48 h. At first amikacin prescription, the time interval was distributed in 4 categories: 48% at 24 h, 4.1% at 30 h, 8.5% at 36 h, and 37.1% at 48 h. As compared to literature guidelines, the rates of overdose and underdose in gentamicin (1.5% and 2.7%) and amikacin (0.3% and 1.0%). They significantly decreased for gentamicin over the study period. In multivariate analysis, the factors significantly associated with GENT overdose were the year of admission, prematurity, length of stay, and duration of the treatment. Conclusion: This prescription strategy ensured a low rate of overdose and underdose, and some benefits of the benchmarking program is suggested.